2020
DOI: 10.1111/exd.14188
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐215‐5p inhibits the proliferation of keratinocytes and alleviates psoriasis‐like inflammation by negatively regulating DYRK1A and its downstream signalling pathways

Abstract: Psoriasis is a chronic inflammatory disease characterized by abnormal hyperproliferation and differentiation. The object of this study is to explore the role of microRNA‐215‐5p in psoriasis‐like inflammation. The expression of miR‐215‐5p was found to be down‐regulated in pro‐inflammatory factor‐stimulated HaCaT cells and imiquimod (IMQ)‐treated skin tissues. Overexpression of miR‐215‐5p suppressed the proliferation and cell cycle progression of HaCaT cells. Further, miR‐215‐5p agomir alleviated the disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In our analysis, multiple mTOR signaling complex molecules are direct targets of miR125b and miR-148 in light of the key role of the axis in abnormal keratinocyte proliferation and differentiation and modulating T cell metabolism, cell proliferation, activation, and differentiation ( 50 , 51 , 72 , 74 , 76 ). EGFR signaling, modulable via miR-215-targeted dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRKA1), is another molecular module that leads to keratinocyte hyperproliferation ( 52 ). The KC innervation pathway comprises Semaphorin 3A (Sema 3A) as a direct target of miR-142-3p, with implications for keratinocyte proliferation, apoptosis, and the production of inflammatory mediators ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis, multiple mTOR signaling complex molecules are direct targets of miR125b and miR-148 in light of the key role of the axis in abnormal keratinocyte proliferation and differentiation and modulating T cell metabolism, cell proliferation, activation, and differentiation ( 50 , 51 , 72 , 74 , 76 ). EGFR signaling, modulable via miR-215-targeted dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRKA1), is another molecular module that leads to keratinocyte hyperproliferation ( 52 ). The KC innervation pathway comprises Semaphorin 3A (Sema 3A) as a direct target of miR-142-3p, with implications for keratinocyte proliferation, apoptosis, and the production of inflammatory mediators ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, although DYRK1A inhibitors have exhibited strong anti-diabetic potential in vivo and in vitro, these compounds face severe challenges. DYRK1A is widely distributed in various tissues throughout the body, and can play a critical role in a variety of biological processes including cell survival and proliferation, such as B-cell survival [ 95 , 96 ], HaCaT cell proliferation [ 97 ], the development and aging of the central nervous system (CNS) [ 98 ], and lipid metabolism [ 99 ] Therefore, we must address the problem to enhance the selectivity of compounds for islet β-cells. Taking EGCG as an example, this can easily pass the blood–brain barrier and exert pharmacological effects on the central nervous system, which is an important obstacle to their further study in the field of diabetic therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 expression in the lesions was reduced by about two-fold after miR-214-3p application. Liu et al [ 63 ] indicated the downregulation of miR-215-5p in cytokine-stimulated HaCaT and imiquimod-treated skin tissue. The treatment of miR-215-5p agomirs on imiquimod-treated mice decreased the number of Ki67-positive cells in the epidermis.…”
Section: Mirnas For Treating Inflammatory Skin Diseasesmentioning
confidence: 99%